Effect of Toona microcarpa Harms Leaf Extract on the Coagulation System. (10th April 2014) - Chen, Hao; Jin, Min; Wang, Yi-Fen; Wang, Yong-Qing; Meng, Ling; Li, Rong; Wang, Jia-Ping; Gao, Li; Kong, Yi; Wei, Ji-Fu
Abstract : Toona microcarpa Harms is a tonic, antiperiodic, antirheumatic, and antithrombotic agent in China and India and an astringent and tonic for treating diarrhea, dysentery, and other intestinal infections in Indonesia. In this study, we prepared ethyl-acetate extract from the air-dried leaves of Toona microcarpa Harms and investigated the anticoagulant activities in vitro by performing activated partial thromboplastin time (APTT), prothrombin time (PT), and thrombin time (TT) assays. Antiplatelet aggregation activity of the extract was examined using adenosine diphosphate (ADP), collagen, and thrombin as agonists, and the inhibitions of factor Xa and thrombin were also investigated. Bleeding and clotting times in mice were used to determine its anticoagulant activities in vivo . It is found that Toona microcarpa Harms leaf extract (TMHE) prolonged APTT, PT, and TT clotting times in a dose-dependent manner and significantly inhibited platelet aggregation induced by thrombin, but not ADP or collagen. Clotting time and bleeding time assays showed that TMHE significantly prolonged clotting and bleeding times in vivo . In addition, at the concentration of 1 mg/mL, TMHE inhibited human thrombin activity by 73.98 ± 2.78%. This is the first report to demonstrate that THME exhibits potent anticoagulant effects, possibly via inhibition of thrombin activity.